Convection in the Labrador Sea - Davis, Russ E (1999)
We hope to describe deep oceanic convection well enough to critically test and guide models used to predict subsurface ocean conditions. Our objective is to use neutrally buoyant float observations to define statistics of convection plume processes (vertical velocity, temperature fluctuations, etc.) over two cooling seasons. These observations will be compared with model predictions relating typical plume properties to physical parameters (surface buoyancy flux, density stratification. etc.) thereby providing an observational test of the models realism and allowing inadequacies to be identified.